Alterations in Blood Ammonium Level and Psychometric Test in Patients with Liver Cirrhosis after a Tempe Diet - Neneng Ratnasari; Siti Nurdjanah (The Indonesian Society for Digestive Endoscopy, 2002)
Background: Hepatic encephalopathy is found in 50-70% cases of liver cirrhosis. Management of hepatic encephalopathy is based on the hypothesis of ammonia and false neurotransmitters. A vegetable diet is the diet of choice, since vegetable proteins have a high biological value, contains non- ammonigenic essential amino acids, and contains fiber. The results of soy fermentation by Rhizopus sp can increase the nutritional value to make it easier for body digestion. Study aim: To determine improvements in hepatic encephalopathy by measuring the ammonium level and determining the psychometric test in patients with liver cirrhosis receiving a tempe diet compared to those receiving a liver diet (conventional diet). Method: This is a random open clinical trial with a proportional stratification according to the Child Pugh criteria. Study subjects are patients with liver cirrhosis who are hospitalized at the Internal Medicine Ward and ambulatory patients at the out-patient Gastro-hepatology Polyclinic of Dr. Sarjito Public General Hospital, from January 1999 to May 2000. The trial was conducted for 20 days, where the first (trial) group is given a tempe diet, while the second (control) group is given liver diet II/III (conventional). Measured outcomes include peripheral blood ammonium level, and psychometric test using the Numeric Connection Test (NCT). Results: In the first group, we found a significant reduction of ammonium level in Child-Pugh A patients and a non-significant reduction in Child-Pugh B/C patients, a non-significant psychometric test improvement in Child-Pugh A patients, and significant psychometric test improvement in Child-Pugh B/C patients. In group II: there is no significant difference in the changes in ammonium level or psychometric test in patients from both Child-Pugh categories. Conclusion: A 20-day tempe diet can reduce ammonium levels and improve results on the psychometric test. Keywords: lever cirrhosis, hepatic encephalopathy, tempe diet, numeric connection test, child-pugh criteria